Paleomagnetism and magnetic fabric of the Eastern Cordillera of Colombia: Evidence for oblique convergence and nonrotational reactivation of a Mesozoic intracontinental rift. Issue 11 (26th November 2014) - Jiménez, Giovanny; Speranza, Fabio; Faccenna, Claudio; Bayona, German; Mora, Andres
Abstract We report the paleomagnetic and magnetic fabric results of 58 sites from Cretaceous‐Miocene marine and continental strata from the Eastern Cordillera (EC) and the Cucuta zone, at the junction between the Santander Massif and the Merida Andes of Colombia. The EC is an intracontinental doubly vergent range inverting a Triassic to Early Cretaceous rift zone. Twenty‐three sites reveal nonsystematic tectonic rotations, including unrotated areas of the EC range with respect to stable South America. Our data show that the EC inverted a NNE oriented rift zone and that the orientation of the Mesozoic rift and the mountain chain roughly correspond. Interestingly, magnetic lineations from anisotropy of magnetic susceptibility analysis do not trend parallel to the chain but rather are oblique to the main orogenic trend. By also considering GPS evidence of a 1 cm/yr ENE displacement of central western Colombia accommodated by the EC, we suggest that the Miocene‐Recent deformation event of this belt arises from ENE oblique convergence reactivating a NNE oriented rift zone. Oblique shortening was likely partitioned into pure dip‐slip shear characterizing thick‐skinned frontal thrust sheets (well known along both chain fronts) and by range‐parallel right‐lateral strike‐slip faults, which have not been identified yet, but likely exist in the axial part of the EC. Finally, the 35° ± 9° clockwise rotation observed in four post‐Miocene magnetically overprinted sites from the Cucuta zone reflects late Cenozoic and ongoing right‐lateral strike‐slip displacement occurring along faults parallel to the Boconó fault system, possibly connected with the right‐lateral faults inferred to exist along the axial part of the EC.